Neuroprotective Effect of Aqueous Extract of Berberis vulgaris L. in a Model of Parkinson's Disease in Rat - F Salar; SA Ziai; S Nasri; M Roghani; M Kamalinejad (Institue of Medicinal Plants, ACECR, 2010)
Background: Parkinson's disease is a neurodegenerative disease of dopaminergic neurons in substancia nigra. Superoxides formation is one of the main etiologies of the disease, and angiotensin converting enzyme inhibitors (ACEIs) are able to suppress superoxide formation. Objective: Berberis vulgaris is an ACE inhibitor and considered for this purpose. Methods: Male rats (n=32) were divided in 4 groups: Sham, Neurotoxin (injection of 6-hydroxydopamine into left hemisphere SNC), Berberis vulgaris aqueous extract (10 mg/kg) and captopril. Berberis and captopril were injected i.p. 7 days before and 3 days after 6-hydroxydopamine injection. Muscle rigidity, apomorphine test, brain protein oxidation and lipid peroxidation as well as serum and brain ACE activity were assayed in all 4 groups. Results: Rotation test with apomorphine in captopril and Berberis groups were significantly lower than neurotoxin group (p=0.002). Lipid peroxidation in captopril was significantly lower than neurotoxin (p=0.013). Captopril and Berberis both inhibited serum ACE activity respectively, but Berberis inhibited brain ACE too. Conclusion: Berberis vulgaris aqueous extract is an ACE inhibitor with anti-parkinsonism effect and should be studied more.